2009
DOI: 10.1073/pnas.0904465106
|View full text |Cite
|
Sign up to set email alerts
|

Selective reciprocity in antimicrobial activity versus cytotoxicity of hBD-2 and crotamine

Abstract: Recent discoveries suggest cysteine-stabilized toxins and antimicrobial peptides have structure-activity parallels derived by common ancestry. Here, human antimicrobial peptide hBD-2 and rattlesnake venom-toxin crotamine were compared in phylogeny, 3D structure, target cell specificity, and mechanisms of action. Results indicate a striking degree of structural and phylogenetic congruence. Importantly, these polypeptides also exhibited functional reciprocity: (i) they exerted highly similar antimicrobial pH opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
81
2
7

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(96 citation statements)
references
References 44 publications
6
81
2
7
Order By: Relevance
“…In our study, among five Gram-negative and two Gram-positive bacterial strains that we tested, crotamine showed an obvious bactericidal activity only against E. coli, with a weak or no activity against all others in the MIC assay, although the time-kill assay revealed a weak activity against S. aureus. Consistent with our results, Yount et al 22 reported the antibacterial activity of crotamine against E. coli, but not S. aureus, using a radial diffusion method. In the same study, the activity against a Gram-positive (Bacillus subtilis) and fungal (Candida albicans) pathogen was also observed with crotamine.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In our study, among five Gram-negative and two Gram-positive bacterial strains that we tested, crotamine showed an obvious bactericidal activity only against E. coli, with a weak or no activity against all others in the MIC assay, although the time-kill assay revealed a weak activity against S. aureus. Consistent with our results, Yount et al 22 reported the antibacterial activity of crotamine against E. coli, but not S. aureus, using a radial diffusion method. In the same study, the activity against a Gram-positive (Bacillus subtilis) and fungal (Candida albicans) pathogen was also observed with crotamine.…”
Section: Discussionsupporting
confidence: 93%
“…Following our comprehensive testing on the antibacterial and cytotoxic properties, we now can unequivocally conclude that crotamine is also a b-defensin-like AMP with a salt-sensitive antibacterial activity. To strengthen our conclusion, an independent study also demonstrated the antibacterial activity of crotamine 22 during the preparation of this manuscript.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…However, as other modes of defensin action are discussed, we cannot exclude other mechanisms of antimicrobial activity exhibited by HisMHBD2 (Yount et al 2009). …”
Section: Antimicrobial Activity Of Expressed Fusion Mature Hbd2 (Hismmentioning
confidence: 99%